Optimization of Modified Yagi-Uda Nanoantenna Arrays Using Adaptive Fuzzy GAPSO. (17th February 2021) - Santos, Pitther N.; Dmitriev, Victor; da Costa, Karlo Q.
Abstract : This paper presents an optimization of the radiation and absorption characteristics of modified Yagi-Uda (YU) nanoantenna arrays. Four geometries of antennas are considered: conventional YU fed by voltage source and transmission line, and YU with a loop element fed by voltage source and transmission line. The numerical electromagnetic simulations of these nanoantennas were made by the method of moments (MoM). The optimization method used is the adaptive fuzzy GAPSO, which consists of hybridization between genetic algorithm (GA) and particle swarm optimization (PSO), with a fuzzy system employed to adapt the inertial weight ω and the acceleration coefficients C1 and C2 of PSO. The optimized results show that the modified YU nanoantennas present better characteristics of gain, directivity, and radiation efficiency than the conventional YU antenna.